2002
DOI: 10.1046/j.1468-3148.2002.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

A Group Treatment for Men with Intellectual Disabilities who Sexually Offend or Abuse

Abstract: Background This report describes a group intervention for men with an intellectual disability who have sexually offended or abused others. The group was in response to referrals to a psychology department. The majority of these individuals had not been subject to legal proceedings. Methods A number of assessments were conducted prior to the group, immediately after the group and at 3-and 6-month follow-up. Results Attitudes consistent with offending reduced after participation for most participants, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 13 publications
3
129
2
Order By: Relevance
“…However, the current results, and previous studies (Gardner, Warren & Gardner, 1977;Koscielak, 1988;Riedel & Milgram, 1970;Wehmeyer, 1994;Wehmeyer & Palmer, 1997) suggest that people with intellectual disabilities, including those who are sex offenders (Rose et al, 2002) may endorse an external locus of control regardless, and this raises some interesting questions for how locus of control is related to treatment outcome for people with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, the current results, and previous studies (Gardner, Warren & Gardner, 1977;Koscielak, 1988;Riedel & Milgram, 1970;Wehmeyer, 1994;Wehmeyer & Palmer, 1997) suggest that people with intellectual disabilities, including those who are sex offenders (Rose et al, 2002) may endorse an external locus of control regardless, and this raises some interesting questions for how locus of control is related to treatment outcome for people with intellectual disabilities.…”
Section: Discussionsupporting
confidence: 44%
“…The NowickiStrickland measure of locus of control was chosen for the current study as this is one of the most widely used measures of locus of control and has been previously used with adults with intellectual disabilities (Wehmeyer, 1994;Wehmeyer & Palmer, 1997) including adults with intellectual disabilities who have a history of sexual offending (Rose et al, 2002), along with sex offenders without an intellectual disability (Fisher et al, 1998).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Each of these papers gave examples of the way in which cognitive distortions are elicited and challenged during treatment and measures of cognitive distortions found reductions which maintained for at least one year follow-up. Rose et al (2002) reported on a 16 week cognitive behavioural treatment for five participants who had perpetrated sexual abuse. They assessed locus of control, cognitive distortions, victim empathy and knowledge of the law and the only significant change was a greater focus on external locus of control after the intervention.…”
Section: Sexual Offending and Inappropriate Sexual Behaviourmentioning
confidence: 99%
“…In reality, most reported interventions for people with intellectual disabilities are multimodal (Day, 2000;Haaven, Little, & Petre-Miller, 1990;Hill-Tout, Thomas, & Dunkerton, 1998;Keating, 2000;Lund, 1992;Murphy, Coleman, & Haynes, 1983;Murphy, Holland, Fowler, & Reep, 1991;Nolley, Muccigrosso, & Zigman, 1996;O'Connor, 1996;Rose, Jenkins, O'Connor, Jones, & Felce, 2002), involving a variety of components and therefore guided by a number of underlying models. Although it is appropriate to formulate interventions for each individual and to provide a comprehensive treatment package that incorporates their needs, these interventions are often published as "ready-to-use" packages.…”
Section: Models Of Offending Used In Interventions For People With Inmentioning
confidence: 99%